RANCANG BANGUN SISTEM INFORMASI INVENTORI OBAT PADA KLINIK RAWAT INAP AGUSAHIDIN MEDICAL DEPOK - Yudha Santoyo; M. Topan Kurniawan (JURNAL LENTERA ICT, 2023)
This research was motivated by the researcher's observations at the Agusahidin Medical Inpatient Clinic in Depok. The drug management process at the clinic is still carried out manually, which causes obstacles in managing drug data such as available drugs, drug input, drug output, and reports. The purpose of creating a new system at the Agusahidin Medical Inpatient Clinic is to facilitate the management of the clinic's drug data. This system was developed using the System Development Life Cycle (SLDC) method. This method is the first information system development method to be used, which is why it is called the traditional method. This method involves several stages, namely conducting surveys, analyzing current processes, determining user requirements, selecting the best solution to the problem, determining the software and hardware, designing a new information system, and implementing the new information system. This drug inventory system is expected to simplify the report generation process, thereby producing more accurate and effective data.